Development and evaluation of triple gene transgenic cotton lines expressing three genes (Cry1Ac-Cry2Ab-EPSPS) for lepidopteran insect pests and herbicide tolerance - Siddiqui, Hamid Anees; Asad, Shaheen; Naqvi, Rubab Zahra; Asif, Muhammad; Liu, Chengcheng; Liu, Xin; Farooq, Muhammad; Abro, Saifullah; Rizwan, Muhammad; Arshad, Muhammad; Sarwar, Muhammad; Amin, Imran; et al. (Scientific reports, 2022)
Cotton is an international agricultural commodity and the main cash crop of Pakistan of which quality and quantity are subject to various whims of nature. Climate change, insect pest complex, and weeds are reducing its productivity. Here, we have developed triple gene cotton containing EPSPS gene along with two Bt toxin genes Cry1Ac and Cry2Ab using a strategy where all three genes are cloned in the same T-DNA, followed by successful cotton transformation via Agrobacterium-mediated transformation. This strategy has been developed to help cotton breeders in developing new cultivars by incorporating these genes into the non-transgenic or single Bt ( Cry1Ac ) gene cotton background where all three genes will inherit together. The expression of all three proteins was confirmed through immunostrips and was quantified through enzyme-linked immunosorbent assay (ELISA). The spatio-temporal expression of Bt protein in different parts of triple gene NIBGE cotton plants was determined. Maximum expression was found in leaves followed by seeds and boll rinds. Insect bioassays with cotton bollworms ( Helicoverpa armigera ), armyworms ( Spodoptera litura ), and pink bollworms ( Pectinophora gossypiella ) showed more than 90% mortality. The best performing line (NIBGE-E2) on the basis of spatiotemporal expression, glyphosate assays, and insect mortality data, was used for event characterization by using the genome sequencing approach. The event was successfully characterized and named NIBGE 20-01. A diagnostics test based on event-specific PCR was developed and its ability to distinguish NIBGE 20-01 event from other commercial transgenic cotton events was confirmed. To confirm stable expression of all three proteins in the field conditions, homozygous transgenic lines were grown in the field and the expression was confirmed through immunostrip assays. It was found that all three genes are expressed under field conditions. To show that all three genes are inherited together upon crossing with local elite cotton lines, the F 1 generation was grown under glasshouse and field conditions. The expression of all three genes was confirmed under field conditions. Our results showed that transgenic cotton with three genes cloned in the same T-DNA can express all genes and can be conveniently transferred into elite cotton lines through a single cross.